Role of middle managers in dealing with hierarchy and network logics: exploration in the context of Sino-Foreign Cooperative University - Li, Jiaxin; Zhang, Xiaojun (Frontiers in Psychology, 2024)
While organizations tend to introduce network mechanism to activate the potential of members in the hierarchical dominated context, it is not clear how individual members deal with the complexity caused by two logics of hierarchy and network. To address this gap, this study focuses on the role of middle managers in collaborating with others in the multiple-logic complexity. We identify three types of collaboration scenarios, top-down, bottom-up, and horizontal, through 27 semi-structured interviews within a Sino-Foreign Cooperative University from 2021 to 2023. Guided by the grounded theory approach, we conceptualize the composite role of middle managers as the translucent hand of explicit and implicit connections, which help us to interpret middle managers' tangibly and intangibly impact under a hybrid organization context. The empirical results also reveal that the boundary perception of authority and responsibility as an important factor determines middle managers' awareness of power involvement in cooperation. The findings extend the understanding of middle managers in network organizations in the higher education context and provide suggestions for the dynamic role of middle managers and hybrid university management in the information age.